Family Functioning: Associations with Weight Status, Eating Behaviors, and Physical Activity in Adolescents - Berge, Jerica M. (2012)
PURPOSE: This paper examines the relationship between family functioning (e.g. communication, closeness, problem solving, behavioral control) and adolescent weight status and relevant eating and physical activity behaviors. METHODS: Data are from EAT 2010 (Eating and Activity in Teens), a population-based study that assessed eating and activity among socioeconomically and racially/ethnically diverse youth (n = 2,793). Adolescents (46.8% boys, 53.2% girls) completed anthropometric assessments and surveys at school in 2009–2010. Multiple linear regression was used to test the relationship between family functioning and adolescent weight, dietary intake, family meal patterns, and physical activity. Additional regression models were fit to test for interactions by race/ethnicity. RESULTS: For adolescent girls, higher family functioning was associated with lower body mass index z-score and percent overweight, less sedentary behavior, higher intake of fruits and vegetables, and more frequent family meals and breakfast consumption. For adolescent boys, higher family functioning was associated with more physical activity, less sedentary behavior, less fast food consumption, and more frequent family meals and breakfast consumption. There was one significant interaction by race/ethnicity for family meals; the association between higher family functioning and more frequent family meals was stronger for non-white boys compared to white boys. Overall, strengths of associations tended to be small with effect sizes ranging from - 0.07 to 0.31 for statistically significant associations. CONCLUSIONS: Findings suggest that family functioning may be protective for adolescent weight and weight-related health behaviors across all race/ethnicities, although assumptions regarding family functioning in the homes of overweight children should be avoided given small effect sizes.